A Numerical Method for Estimating Strut Forces in Multi-Braced Excavation Systems - Nguyen, Tong; Le, Phuong (Journal of Technical Education Science, 2023)
The paper discusses the development of a numerical method for a multi-braced excavation to estimate strut forces. Two different software were used in the proposed method. Equivalent strut forces were calculated by plane strain analysis on Plaxis 2D. The number of Etabs models built corresponds to the number of strut levels. Loads acting on waler beams in these structural models were derived from the results of equivalent strut forces on the Plaxis 2D model. The results of the proposed method were compared with those of a full 3D analysis. This method ensures the force equilibrium with an error of less than 5% as compared with the total strut forces in the 3D calculation. Due to the corner effect not take into account, the corner strut internal forces in the proposed method are usually larger than those in the 3D analysis, while the internal forces of the middle struts seem to be the opposite. Although the differences have a wide variation, the average error is 35%. However, the results from the proposed method are conservative. The proposed method is useful for practicing engineers, especially in the primary design stage of multi-braced excavation with a complex-shaped plan.